Study of Mean Diameter of Superior Cerebellar Peduncles in Bangladeshi Cadavers (Journal of Enam Medical College, 2016)
Background: The neuronal organisation of the cerebellum has been studied in details by many researchers. But most of these have been performed on animals and diameter of superior cerebellar peduncle in humans remains inadequately studied. It has been observed by various workers that dimensions of different organs in Bangladeshi population vary from those of Western population.Objective: Aim of the present work was to measure diameter of superior cerebellar peduncle to make a standard for Bangladeshi population.Materials and Methods: This observational study was done by using nonprobability sampling technique and performed by examining 63 cerebellum. Out of them 40 postmortem human cerebellums were collected from Bangladeshi cadavers of both sexes (male 25 and female 15) aged 5 to 60 years and 23 cerebellums from caesarian section of intrauterine death cases of both sexes (male 14 and female 9) aged 34 to 41 weeks of gestation. Specimens were collected from dead bodies autopsied on different dates from April to September 2009 at the autopsy laboratory of Department of Forensic Medicine and prenatal cases from Gynaecology and Obstetrics Department of Mymensingh Medical College & Hospital, Mymensingh. The collected specimens were grouped into three age groups - Group A (28 to 42 weeks of gestation), Group B (5 to 30 years) and Group C (31 to 60 years). The diameters of the superior cerebellar peduncles of both cerebellar hemispheres were measured by using slide calipers and expressed in millimeter (mm). The measurement was taken after fixation into 10% formol saline.Results: The mean (± SD) diameters of right superior cerebellar peduncle in Group A was 4.96 ± lAO, in Group B 6.83 ± 1046 and in Group C was 6.61 ± 1.34 mm. The mean (± SD) diameters of left superior cerebellar peduncle in GroupA was 4.87 ± 1.25, in Group B 6.79 ± 1045 and in Group C 6048 ± 1.37 mm.Conclusion: No significant difference was observed between mean diameters ofright and left superior cerebellar peduncles.J Enam Med Col 2016; 6(3): 148-151